Improving of Geometric Precision in the Manufacture of Circular Holes Using Technology WEDM - Straka, Luboslav; Dittrich, Gabriel (International Journal of Engineering and Management Sciences, 2019)
WEDM technology is among the final technology. It is characterized by the high quality of the machined surface. Therefore, a small geometric deviation from the desired shape, position, orientation or run out may have a significant impact on the functionality of the finished component. Its range is largely influenced by the accuracy of the applied electroerosion device, the precision of the workpiece and tool setting, the machining method, but also the combination of each other and the adjustment of all process parameters. They result in the final quality of the machined surface not only in terms of roughness parameters but also in terms of geometric precision of the machined surface. The aim of the paper was to describe the possibilities of improving the geometrical accuracy of WEDM with thin brass electrodes. At the same time, it contributes to an existing database of knowledge that defines the influence of selected aspects on the geometrical accuracy of the machined area in the production of circular openings.